2020
DOI: 10.33945/sami/ajca.2020.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulation Layer Composite and Water Adsorption on Bonding Performance in Heat Barriers

Abstract: Thermal insulation layer in solid rocket motors is a vital component during the rocket flight. Many factors can affect the performance of this insulation layer. Bonding property between rocket propellant and the thermal insulation layer are examined in this study. Hydroxyl terminated polybutadiene (HTPB) and isophorone diisocyanate (IPDI) as a curative was chosen as the most common type of rocket propellant. The effect of two types of polymeric insulation layer such as nitrile butadiene rubber (NBR) and ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…From this point of view, PU-EHSM is better as insulation materials because insulator and propellant are of the same chemical nature. Interfacial bonding of NBR and EPDM to HTPB/IPDI composite propellant revealed that both types of insulation layers considerably decreased bonding [64]. This can be expected, considering the different chemical nature of EPDM and NBR compared to the PU-cured propellant.…”
Section: Bonding Of Ehsm To Composite Propellantmentioning
confidence: 66%
“…From this point of view, PU-EHSM is better as insulation materials because insulator and propellant are of the same chemical nature. Interfacial bonding of NBR and EPDM to HTPB/IPDI composite propellant revealed that both types of insulation layers considerably decreased bonding [64]. This can be expected, considering the different chemical nature of EPDM and NBR compared to the PU-cured propellant.…”
Section: Bonding Of Ehsm To Composite Propellantmentioning
confidence: 66%
“…On the other hand, the lower the functionality, the higher the molecular mass, and the more elastic network is obtained for a given number of functional groups. Network structure can be regulated through the isocyanate/hydroxyl ratio [88]. Temperature-humidity conditions are fundamental in attaining the proper cure [89].…”
Section: Curing Kinetics Of Htpb With Isocyanates and "Potlife"mentioning
confidence: 99%
“…A layer of insulation material is always needed to provide thermal protection from combustion gases over the in-ternal surface of the motor case [5][6][7][8]. This layer is typically vulcanized rubber consisting of filling material.…”
Section: Introductionmentioning
confidence: 99%